TCAD modeling of bias temperature instabilities in SiC MOSFETs. (November 2021) - Carangelo, G.; Reggiani, S.; Consentino, G.; Crupi, F.; Meneghesso, G.
Highlights: TCAD modeling of BTI in SiC-MOSFET. SiO2 /SiC interface charge trapping. Extended non-radiative multiphonon theory. Reliability issues in SiC-MOSFET. Abstract: TCAD simulations of SiC power MOSFETs have been performed to study the dependence of positive-bias temperature instability (PBTI) on temperature and electric field. The model used to describe the kinetics of the transition rates between neutral and charged traps is the extended Non-Radiative Multi Phonon (eNMP). Connections between oxide defect configurations at the interface with SiC substrate have been made. Validation against experiments is shown.